(untitled) (CITITORI ȘI LECTURI. CERCETĂRI COMPARATISTE, 2026)
Georgiana Tudor explores the modern Hell in Pär Lagerkvist’s novel Barabbas, linking it to Kierkegaard’s "indirect communication." The study analyzes three infernal spaces—the copper mine, the catacombs, and the fire of Rome—as stages of a psychological descent. Through these encounters with darkness and his double, Sahak, Barabbas moves from indifference to self-awareness. Ultimately, the author argues that Barabbas’s final surrender represents a conscious act of freedom, achieving an authentic existence despite perpetual ambiguity. THIS ABSTRACT IS GENERATED WITH ARTIFICIAL INTELLIGENCE.